1967
DOI: 10.1002/ange.19670790315
|View full text |Cite
|
Sign up to set email alerts
|

Umlagerungen im Triasteran‐System

Abstract: Reduktion von (2) rnit NaBH4 in Methanol verlauft stereospezifisch von der p-Seite her und ergibt die 1,2:5,6-Di-0isopropyliden-a-D-gulofuranose (3) [Ausbeute 60 %, Fp = 105-106"C, [or]: = +7,5 (c = 1 in CHC13)], die nach Hydrolyse mit Lewatit S 100 H+rzl (30 min, 9OoC) D-Gulose (4) mit quantitativer Ausbeute und diinnschichtchromatographischer Reinheit ergibt [identifiziert als Phenylhydrazon 131; Fp und Misch-Fp rnit aus authentischer D-Gulose[41 hergestellter Vergleichsprobe 142-143 "C; (Lit. 131: F p = 143… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1967
1967
2000
2000

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(2 citation statements)
references
References 2 publications
0
2
0
Order By: Relevance
“…For a product study, 6-OTs was solvolyzed in methanol and TFE buffered with 2,6-lutidine. Gas chromatography indicated that the products were 2-bicyclo[3.2.2]nonene ( 10 ), 2-bicyclo[3.3.1]nonene ( 11 ), ,, tricyclo[3.3.1.0 2,8 ]nonane ( 12 ), 2-R-bicyclo[3.2.2]nonane [ 6-R : 6-OMe (R = OMe), 6-OTFE (R = OCH 2 CF 3 )], exo -2-R-bicyclo[3.3.1]nonane [ 8-R : 8-OMe (R = OMe), 8-OTFE (R = OCH 2 CF 3 )], and a small amount of an unidentified ether (Scheme ). The yields of the products are shown in Table .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…For a product study, 6-OTs was solvolyzed in methanol and TFE buffered with 2,6-lutidine. Gas chromatography indicated that the products were 2-bicyclo[3.2.2]nonene ( 10 ), 2-bicyclo[3.3.1]nonene ( 11 ), ,, tricyclo[3.3.1.0 2,8 ]nonane ( 12 ), 2-R-bicyclo[3.2.2]nonane [ 6-R : 6-OMe (R = OMe), 6-OTFE (R = OCH 2 CF 3 )], exo -2-R-bicyclo[3.3.1]nonane [ 8-R : 8-OMe (R = OMe), 8-OTFE (R = OCH 2 CF 3 )], and a small amount of an unidentified ether (Scheme ). The yields of the products are shown in Table .…”
Section: Resultsmentioning
confidence: 99%
“…A solution of 6-OTs (130 mg, 0.46 mmol) in MeOH (23 mL) containing 0.05 M 2,6-lutidine was heated at 50 °C for 10 half-lives. The product distribution was determined by GLC, which indicated that products were 2-methoxybicyclo[3.2.2]nonane ( 6-OMe ), exo -2-methoxybicyclo[3.3.1]nonane ( 8-OMe ), 2-bicyclo[3.2.2]nonene ( 10 ), 2-bicyclo[3.3.1]nonene ( 11 ), tricyclo[3.3.1.0 2,8 ]nonane ( 12 ), and an unidentified ether (Table ). Most of the solvent was removed by distillation and to the residue was added ether.…”
Section: Methodsmentioning
confidence: 99%